EMERGENCY DISTANCE EDUCATION AS A SOCIAL COMMUNICATION STRATEGY IN UKRAINE AND THE WORLD - Nadiya Figol; Yuriy Kolisnyk; Tetiana Faichuk; Bogdan Figol (Інтегровані комунікації)
The article addresses the relevant topic of emergency distance learning in Ukraine and worldwide during crises such as pandemics, military conflicts, and natural disasters. The aim is to explore and analyze the concepts of "distance education" and "emergency distance learning," focusing on their main characteristics, differences, and specific implementation features. The primary objectives of the article include examining scientific and practical approaches to the definitions and identifying key distinctions. The research methodology is based on a qualitative approach, employing literature review, content analysis, and case study methods.